Experimental modeling of adjacent parallel shield tunnels subjected to train-induced vibration loads. (October 2021) - Zhang, Junchen; Yan, Qixiang; Yang, Kai; Sun, Minghui
Previous studies have performed numerical simulations of adjacent parallel shield tunnels under train-induced vibration loads. However, few experimental studies have been performed for the interaction mechanisms. In this study, experimental modeling is conduced to explore the interaction of adjacent parallel shield tunnels subjected to different train-induced vibration loads. A new Hilbert-Huang transform (HHT) is applied to obtain the instantaneous responses of tunnels. The results show that the acceleration of the tunnel follows the trend of the train load curve. The peak accelerations of the tunnels experience a unimodal distribution along the train speed, while the dominant frequencies of the tunnels follow a bimodal distribution. The interaction between the adjacent parallel tunnels is significant. The transform of the vibration loads to the adjacent tunnel is through the soil below the tunnel. The farther away from the train load is, the greater the train speed corresponding to the dominant frequency peak.